Medication-Related Problems in Liver Transplant Recipients in the Outpatient Setting: A Dutch Cohort Study - Mulder, Midas B.; Borgsteede, Sander D.; Darwish Murad, Sarwa; Landman, Catelijne S.; Metselaar, Herold J.; Hunfeld, Nicole G.M. (Frontiers in Pharmacology, 2021)
After liver transplantation (LTx), adherence to immunosuppressive medication and avoidance of contra-indicated drugs is essential for long-term survival. This study aimed to investigate the prevalence, types and severity of medication-related problems (MRPs) and interventions initiated by a clinical pharmacist (CP) in a cohort of LTx recipients in the outpatient setting. This study was a retrospective, observational study in LTx recipients that visited the outpatient clinic for an annual check-up. A 20-minutes consultation with a CP consisted of medication reconciliation and consultation about medication, adherence, and adverse drug reactions (ADRs). Discrepancies between actual and intended drug use, and MRPs were identified and the severity of MRPs was assessed. Potential interventions were discussed with the patient and the treating physician and evaluated after one year. The CP counseled 64 LTx recipients and found 96 discrepancies in 37 patients. Most discrepancies (60.4%) concerned missing medications. In total, 98 MRPs were identified in 53 patients (median 2; range 1-5 per patient). Most frequent MRPs were: ADRs (22.4%), nonadherence (19.3%), unnecessary drugs (16.3%) and undertreatment (12.2%). Interventions most frequently proposed included optimization of dosage regimen (21.2%), individualized recommendation regarding compliance (16.8%) and drug discontinuation (12.4%). After one year, 79% of the patients experienced no compliance issues and 93% of the patients used no drugs with indication issues anymore. The CP in an outpatient monitoring program for LTx recipients can signal relevant discrepancies and MRPs. This leads to interventions that are accepted by both the patients and the physicians, with a positive effect after one year.